2015
DOI: 10.1007/s00221-015-4371-0
|View full text |Cite
|
Sign up to set email alerts
|

What you see is what you get: motor resonance in peripheral vision

Abstract: The first aim of this event---related fMRI study was to identify the neural circuits involved in imitation learning. We used a rapid imitation task where participants directly imitated pictures of guitar chords. The results provide clear evidence for the involvement of dorsolateral prefrontal cortex, as well as the fronto---parietal mirror circuit (FPMC) during action imitation when the requirements for working memory are low. Connectivity analyses further indicated a robust connectivity between left prefronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
4
17
0
Order By: Relevance
“…Thus, one possible reason for the small effect size may be the variation in observation sites and methods that observers used during gait observation. In support of this speculation, several recent TMS studies demonstrated that directing an observer's visual attention to a fixed part of an observed movement or action-relevant object enhances corticospinal excitability during the observation of thumb abduction/adduction movements [59] and hand grasping actions [60][61][62]. Given these definite effects of an observer's overt attention on motor resonance, it can be assumed that the results obtained in this study were also substantially affected by the participants' attention.…”
Section: Effects Of Visual Experience And/or Intention To Imitate On supporting
confidence: 74%
“…Thus, one possible reason for the small effect size may be the variation in observation sites and methods that observers used during gait observation. In support of this speculation, several recent TMS studies demonstrated that directing an observer's visual attention to a fixed part of an observed movement or action-relevant object enhances corticospinal excitability during the observation of thumb abduction/adduction movements [59] and hand grasping actions [60][61][62]. Given these definite effects of an observer's overt attention on motor resonance, it can be assumed that the results obtained in this study were also substantially affected by the participants' attention.…”
Section: Effects Of Visual Experience And/or Intention To Imitate On supporting
confidence: 74%
“…Schain et al’s (2012) findings may be due to the use of a unique stimulus of the face as a distractor. In accordance with Leonetti et al (2015), MNS activation is enhanced by peripheral vision. In other words, OI should occur in a situation where the observer’s attention is not directed to an action itself (i.e., the inattentive observation condition).…”
Section: Introductionsupporting
confidence: 65%
“…On the other hand, it is possible to form a different interpretation. Given that motor resonance is thought to reflect MNS activation to facilitate in peripheral vision (Leonetti et al, 2015), and that there may be a higher cognitive mechanism for self-other distinction controlling our self-agency judgment (Brass et al, 2009), our result might be explained by another mechanism [i.e., the agency-judgment mechanism including TPJ suggested by Brass et al (2009)] even though MNS is actually activated in the inattentive condition. However, our study did not directly modulate and measure MNS, so it cannot be mentioned properly.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Also magnetoencephalic (MEG) response to point-light biological motion displays, although largely independent of attention, seems to reflect further processing when stimuli are attended [28]. In neurophysiological terms, Leonetti and colleagues [35] asked participants to gaze upon a fixation point while covertly attending to an action sequence, in order to test whether presenting an action in peripheral vision could differently modulate motor excitability. The results showed that, even if the action viewed in peripheral vision—and then covertly attended—was effective in modulating the excitability of motor pathways, the accuracy of the motor response was low and rough.…”
Section: Introductionmentioning
confidence: 99%